Peran Guru Ngaji dalam Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Al-Qur’an Hadits di MI Raudlatul Wathani Taman Sari Batunampar.: The Role of Quran Teachers in Improving Student Learning Achievement in the Al-Quran and Hadith Subject at MI Raudlatul Wathani Taman Sari, Batu Nampar Village - M. Saipul Watoni; Nasrullah; Supetra (Pendidikan Al-Gafari, 2026)
This study aims to determine the role and obstacles of Qur’an teachers in improving student learning achievement in the Al-Qur'an Hadits subject. This study uses a qualitative descriptive method to obtain information on the role and obstacles of Qur’an teachers in improving student learning achievement in the Al-Qur'an Hadits subject. This study uses unstructured interviews and structured interviews by researchers with the Principal, Al-Qur'an Hadith Teachers, Koran teachers, parents of students and students. The results of this study are that there are several roles of the Qur’an Teacher, including the Qur’an Teacher as someone who provides the basis for students to become proficient in reading and writing the Qur’an and Hadits, the Qur’an Teacher as a director, instiller and guide for students in having good morals towards parents, teachers and peers, the Qur’an Teacher as a motivator for students to continue learning in deepening the Qur’an and Hadits, the Qur’an Teacher as a controller in the learning process at the Qur’an study place, the Qur’an Teacher as a mediator and solution provider in religious problems, especially in the problem of how to read the Qur’an and Hadits properly and correctly, the Qur’an Teacher as a role model for his students and, the Qur’an Teacher as an instiller of discipline in students. Meanwhile, the obstacles faced by Qur’an teachers in improving student learning achievement in the Al-Quran and Hadits subject are the lack of interest and enthusiasm of students in reciting the Qur’an, students are too busy playing with their cellphones so that they are negligent in reciting the Qur’an, the students' residential environment is far from the Qur’an study place, the lack of support and motivation from students' parents so that students are lazy to go to Qur’an study, Qur’an teachers cannot be too firm in responding to students who are lazy and naughty in reciting the Qur’an because of human rights.